2014
DOI: 10.3189/2014jog13j199
|View full text |Cite
|
Sign up to set email alerts
|

Location of cation impurities in NGRIP deep ice revealed by cryo-cell UV-laser-ablation ICPMS

Abstract: ABSTRACT. In polar ice sheets, the average grain size varies with depth. Ice grain size increases due to several factors including ice temperature and impurity content, which in turn varies with climate. The effect of impurities on grain growth is thought to be crucial but has never been observed experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 59 publications
(101 reference statements)
2
44
0
Order By: Relevance
“…Furthermore, one of the very few studies which found evidence for a connection of spatial distribution of impurities along grain boundaries reported this evidence as a characteristic of "clean" interstadial ice (Della Lunga et al, 2014). Four samples were analyzed: two from the EDML ice core (Antarctica) and two from the NEEM ice core (Greenland).…”
Section: Methods and Sample Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one of the very few studies which found evidence for a connection of spatial distribution of impurities along grain boundaries reported this evidence as a characteristic of "clean" interstadial ice (Della Lunga et al, 2014). Four samples were analyzed: two from the EDML ice core (Antarctica) and two from the NEEM ice core (Greenland).…”
Section: Methods and Sample Materialsmentioning
confidence: 99%
“…In contrast, EDX experiments by Cullen and Baker (2001), Barnes et al (2002), Barnes (2003), Baker et al (2003) and Iliescu and Baker (2008) found traces of sodium, chlorine and sulfur in filaments, which would grow out of grain boundaries after controlled surface sublimation of natural ice samples. Della Lunga et al (2014) analyzed the distribution of a variety of elements in discrete samples from the glacial part of the NGRIP ice core using UV-LA-ICPMS. No correlation was found between impurities and grain boundaries in cloudy bands, but the authors observed concentration peaks at grain boundaries in the cleaner parts of the ice.…”
Section: Introductionmentioning
confidence: 99%
“…, Della Lunga et al . ). Because many of the analyses carried out over this period were line‐scans (tracks) across relatively large growth‐banded carbonate samples – to our knowledge – we present the first extensive data set of laser ablation line‐scan (‘track’) data of RMs.…”
mentioning
confidence: 97%
“…While these methods offer very accurate results, they can be time intensive (∼hours) and thus often limit the spatial resolution (e.g., 50 samples per meter in [14]). More recently, a new approach to chemistry sampling using a laser to ablate the ice is providing semi-automated sampling at much higher spatial resolutions than previously possible (e.g., sub-mm resolution [15,16]). …”
Section: Introductionmentioning
confidence: 99%